Penyuluhan dan Pelatihan Pengolahan Makanan Bergizi Bagi Kader PKK RW 04 Kelurahan Badean - Ningsih, Indah Yulia; Hidayat, Mochammad Amrun; Suryaningsih, Ika Barokah; Kuswandi, Bambang (STMIK Royal, 2025)
The level of health significantly influences the quality of human resources. The family, being the most basic unit of society, has a significant impact on enhancing health outcomes. A mother is suitable for this role, as she is responsible for caring for the entire family. Kader PKK (members of the Family Welfare Movement, a community-based women's organization in Indonesia) of RW 04 in Badean Village, Bondowoso District, Bondowoso Regency has an opportunity to enhance their potential through women's empowerment. The distribution of educational and economic levels among people in RW 04, Badean Subdistrict, is uneven, resulting in a disparity in their health status as well. This service activity focuses on empowering women through the implementation of the Participatory Rural Appraisal (PRA) method. The aim is to enhance the quality of community health by conducting counseling and training on preparing nutritious food using Moringa leaves, which are readily accessible to the population. This service activity has enhanced the knowledge and skills of Kader PKK of RW 04 in processing nutritious meals. They can also disseminate the knowledge they have acquired to mothers in their surroundings, thus improving the effectiveness of initiatives to empower women in the healthcare sector. Keywords: Counseling and training; nutritious meals; kader PKK Abstrak: Salah faktor yang berperan besar terhadap kualitas sumber daya manusia adalah tingkat kesehatan. Keluarga sebagai kelompok sosial terkecil dalam masyarakat memegang peran penting dalam perbaikan status kesehatan. Peran ini dapat dipegang oleh seorang ibu karena ibulah yang bertugas merawat seluruh keluarga. Salah satu kelompok yang berpeluang dikembangkan potensinya melalui pemberdayaan wanita adalah kader PKK (Pembinaan Kesejahteraan Keluarga) RW 04 Kelurahan Badean Kecamatan Bondowoso Kabupaten Bondowoso. Tingkat pendidikan dan perekonomian warga di lingkungan RW 04 Kelurahan Badean tidak merata, sehingga status kesehatannya juga belum merata. Pada kegiatan pengabdian ini dilaksanakan upaya pemberdayaan perempuan menggunakan metode PRA (Participatory Rural Appraisal) berupa upaya peningkatan kualitas kesehatan masyarakat melalui kegiatan penyuluhan dan pelatihan pembuatan makanan bergizi berbasis daun kelor yang mudah didapat di sekitar lingkungan warga. Dengan adanya kegiatan pengabdian ini pengetahuan dan keterampilan kader PKK RW 04 mengenai pengolahan makanan bergizi menjadi meningkat. Para kader juga dapat menyampaikan ilmu yang diperolehnya kepada para ibu di lingkungannya, sehingga upaya pemberdayaan perempuan dalam bidang kesehatan menjadi lebih optimal.Kata kunci: Penyuluhan dan pelatihan; makanan bergizi; kader PKK